2019
DOI: 10.1002/jnm.2591
|View full text |Cite
|
Sign up to set email alerts
|

180 to 240 GHz broadband, EM‐based power amplifier using 0.5‐μm InP DHBT technology

Abstract: This paper reports a power amplifier (PA) terahertz monolithic integrated circuit (TMIC) from 180 to 240 GHz. This amplifier is fabricated from a 0.5-μm indium phosphide double heterojunction bipolar transistor (InP DHBT) technology, jointly with a thin-film microstrip wiring environment. Furthermore, an electromagnetic (EM) simulation method is proposed for the parameter extraction of InP DHBTs and amplifier design. This five-stage amplifier has >6.1 dB S 21 gain from 180 to 240 GHz, peaks 10.4 dB S 21 gain a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
(19 reference statements)
0
1
0
Order By: Relevance
“…In the design of InP HBT‐based circuits, Cui et al reported a broadband subharmonic mixer in the frequency range of 199 to 238 GHz by combining the diode SPICE model and 3D full‐wave electromagnetic (EM) model. Li et al proposed an EM simulation‐based method for InP HBTs model parameter extraction, which is applied to 180 to 240 GHz amplifier design. Passive device models in CMOS technology are quite complicated due to the small area.…”
mentioning
confidence: 99%
“…In the design of InP HBT‐based circuits, Cui et al reported a broadband subharmonic mixer in the frequency range of 199 to 238 GHz by combining the diode SPICE model and 3D full‐wave electromagnetic (EM) model. Li et al proposed an EM simulation‐based method for InP HBTs model parameter extraction, which is applied to 180 to 240 GHz amplifier design. Passive device models in CMOS technology are quite complicated due to the small area.…”
mentioning
confidence: 99%